Defining work tools : studying effects of digitalising work tools - Helmrich, Robert [Herausgeber]; Tiemann, Michael [Herausgeber] (Bundesinstitut für Berufsbildung, 2020)
"Change in the world of work, be it in the form of digitalisation or other, is often discussed in broad terms of possible losses of jobs or huge restructurings of whole branches. Seldom do we look at what workers actually do at their workplaces - and how. But obviously technological change will affect the things we work with, our work tools. This reader combines empirically grounded insights into how changes in work tools affect our work and how we react to it. In this sense it is a 'hands-on' approach to find out more about the impacts digitalisation might have on qualification and the labour market. Work tools can be used to link analytical perspectives to investigate the effects of digitalisation on workplaces and employment, to understand the demand for specific competences within occupations and also to arrive at a workspace-specific understanding of said changes." (BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; G 2.3.4 Qualifikationswandel; Arbeitswelt; Arbeitsmittel; Digitalisierung; Auswirkung; Qualifikationswandel; Beschäftigung